Некоторые геометрические аспекты цилиндрических передач Новикова ДЛЗ - Матюшенко, Николай Васильевич; Федченко, Анна Валерьевна; Бережной, Виталий Александрович; Калинин, П. Н. (НТУ "ХПИ", 2014)
В статье получено уравнение поверхности зубьев цилиндрических передач Новикова с двумя линиями зацепления (ДЛЗ) с циклоидальной продольной формой, нарезанных резцовой головкой. Форма зуба является огибающей однопараметрического семейства мгновенных положений исходного контура инструмента. Построен алгоритм вычисления толщины зуба.

The paper obtained the equation of the teeth of Novikov cylindrical gears with two lines of engagement (DLA) with longitudinal cycloidal form, chopped the cutting head. Tooth shape is the enve-lope of one-parameter family of the instantaneous position of the initial contour of the tool. Constructed an algorithm for calculating the thickness of the tooth.
Some aspects of geometric Novikov’s cylindrical gears
Keywords: две линии зацепления; толщина зуба; spurgear; Novikov gear; two lines of engagement; tooth thickness